2001
DOI: 10.1046/j.1365-2222.2001.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of new sensitizations in monosensitized subjects submitted to specific immunotherapy or not. A retrospective study

Abstract: Specific immunotherapy was observed retrospectively to reduce new sensitizations in monosensitized subjects suffering from respiratory allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
5
14

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(157 citation statements)
references
References 33 publications
2
136
5
14
Order By: Relevance
“…First, SIT can modify the natural history of allergic disease, as confirmed in rigorously conducted trials (13,14). Second, SIT can prevent the onset of new sensitizations, as demonstrated clearly in children in several studies (15,16). Third, SIT even maintains its clinical efficacy years after discontinuation.…”
Section: Discussionmentioning
confidence: 85%
“…First, SIT can modify the natural history of allergic disease, as confirmed in rigorously conducted trials (13,14). Second, SIT can prevent the onset of new sensitizations, as demonstrated clearly in children in several studies (15,16). Third, SIT even maintains its clinical efficacy years after discontinuation.…”
Section: Discussionmentioning
confidence: 85%
“…Our search strategy identified 1378 unique publications, including over 338 peer-reviewed studies published from inception to June 30, 2015 finally retrieved , of which 18 met the inclusion criteria (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). We excluded the Jacobsen study (38), because the outcome was reported in a subgroup of patients regardless of the treatment received, the Eifan (39) Acquistapace (40), Szepfalusi (41), and Shao (42) studies because they were not long-term studies (<3 years of treatment/follow-up).…”
Section: Resultsmentioning
confidence: 99%
“…9,47 El efecto preventivo del desarrollo de nuevas sensibilizaciones fue demostrado tanto para la modalidad subcutánea 48,51 como sublingual. 52 Los cambios inmunológicos provocados por la inmunoterapia se han observado desde los primeros años de la vida.…”
Section: Intervención Inmunológica Inmunoterapia Alérgeno Específicaunclassified
“…En un estudio en niños con rinoconjuntivitis sensibles a pólenes de gramíneas, la ITSL redujo la incidencia de asma 56 y un ensayo abierto con pólenes y ácaros de 3 años de duración demostró su capacidad para reducir la hiperreactividad bronquial inespecífica y el comienzo de nuevas sensibilizaciones y de asma persistente 51 (Tabla 2). Por su capacidad preventiva, la inmunoterapia es la única modalidad terapéutica capaz de m o d i f i c a r l a e v o l u c i ó n n a t u r a l d e l a s enfermedades alérgicas en la infancia.…”
Section: Tabla 3: Estado Del Arte De Las Medidas Higiénico-dietéticasunclassified